TEACHING LITERATURE THROUGH POETRY: A SHIFTING READING ORIENTATION FROM EFFERENT TO AESTHETIC - Nirma Herlina (Universitas Islam Sultan Agung, 2016)
There is a paradigm shifting in teaching literature from transmission totransactional. However, most of Indonesian English teachers in teachingliterature still apply transmission approach which shows they are not readyyet for the changing. This article attempts to show the shift of paradigm inreading orientations and its implications in teaching literature through poetryby describing the writer’s experience in learning literature through poetry.Discussing six important points, this essay is purposed to give alternativeteaching-learning literature which would provide good points for students aswell as teachers.Keywords: paradigm shift, reading orientation, teaching literature, poetry,efferent, aesthetic